Dinâmica populacional do psilídeo-de-concha Glycaspis brimblecombei (Moore, 1964) (Hemiptera: Psyllidae) e de seu parasitóide Psyllaephagus bliteus (Hymenoptera: Encyrtidae) em floresta de Eucalyptus camaldulensis - Ferreira Filho, Pedro José [UNESP]; Wilcken, Carlos Frederico [UNESP]; Oliveira, Nádia Cristina de [UNESP]; Dal Pogetto, Mário Henrique Ferreira do Amaral [UNESP]; Lima, Alexandre Coutinho Vianna [UNESP] (Universidade Federal de Santa Maria (UFSM), 2008)
O psilídeo-de-concha, Glycaspis brimblecombei, é uma praga exótica específica de Eucalyptus, que causa desfolha, secamento de ponteiros e ramos, podendo levar as árvores à morte. O parasitóide Psyllaephagus bliteus é indicado como principal agente no controle biológico desta praga. Portanto, o monitoramento adequado de as ambas espécies por um método eficiente de amostragem facilitaria o manejo para uma futura tomada de decisão. Devido à falta de informações referentes ao seu comportamento em plantações extensivas de eucalipto no Brasil, este trabalho teve como objetivo estudar as populações de G. brimblecombei e de P. bliteus em florestas de Eucalyptus camaldulensis, utilizando armadilhas amarelas para determinação de sua flutuação populacional e correlacionado-as com variáveis meteorológicas (temperatura e precipitação). A determinação da flutuação populacional (53 pontos amostrais) foi realizada em talhão de 19ha com E. camaldulensis em Luíz Antônio, SP, em 10avaliações quinzenais, entre janeiro e junho de 2005. As populações de ambas as espécies apresentaram correlação inversamente proporcional em função da temperatura e não há correlação com a precipitação no período avaliado.

Psyllids are one most widespread group of pests, causing severe damage on agricultural and forestry systems. The recently discover about occurrence of red gum lerp psyllid Glycaspis brimblecombei Moore (Hemiptera: Psyllidae), in Brazil is, nowadays a serious problem in Eucalyptus forests, mainly in E. camaldulensis. The psyllid specific parasitic wasp Psyllaephagus bliteus Riek (Hymenoptera: Encyrtidae) is the main biological control agent of this pest. Thus, the adequate monitoring of both species by efficient sampling method would facilitate a future decision making. Due to economic importance, this study aimed to evaluate G. brimblecombei and P. bliteus populations in Eucalyptus camaldulensis plantation, using yellow traps to determinate population fluctuation with weather interactions (temperature and rainfall). The study of the pest and parasitoid population (53 sampling dates) was carried out on E. camaldulensis plantations in 19ha area in Luíz Antônio municipality (SP, Brazil), with quarterly samplings, between January and June, 2005 (ten sampling dates). This research indicated that populations had an inversely proportional correlation subject according to the temperature. However, there is no correlation between both species with the rainfall in the evaluated period.
Population dinamics of red gum lerp psyllid, Glycaspis brimblecombei (Moore, 1964) (Hemiptera: Psyllidae) and its parasitoid, Psyllaephagus bliteus (Hymenoptera: Encyrtidae), in Eucalyptus camaldulensis plantation
Keywords: eucalipto; praga florestal; inimigo natural; controle biológico; proteção florestal; eucalypt; forest pest; natural enemy; biological control; forest protection